The Implementation of Service-Dominant Logic in Designing Brand Management Plans to Maintain Leadership in Dr. YAP EYE Hospital - Brodjonegoro, Basilius Prabawa; Nasution, Reza Ashari (The Indonesian Journal of Business Administration, 2012)
A privately-owned eye hospital operating since 1923 is beginning to take steps in managing its brand. The approach is based on Service-Dominant Logic, to ensure patient-orientation and relevance. Research was conducted to determine the factors that determine patients’ hospital choice, hospital quality evaluation, and the hospital’s performance in those factors.The results suggested that there are six factors considered when choosing a hospital: the perceived ability to cure illnesses, the skill of the doctors, the specialization of the hospital, the complete equipment owned by the hospital, the experience level of the doctors, and the extent of the patient’s trust to the hospital. The hospital performs well in all six factors.Among the many factors considered when evaluating a hospital’s quality, there are three factors which have higher importance than average, but the hospital’s performance is lower than average: speed of treatment, established trust, and friendliness.The hospital is bound by the Code of Ethics of Indonesian Hospital, in conducting its promotional activities. The hospital is advised to communicate its competence in the six most important decision factors; it is done by placing posters and information boards throughout the hospital, and by opening a new media for communication with the public: online social media (Facebook).The hospital is advised to improve its quality by forming an Information Center, providing Patient Notification Service, simplifying the administrative process, and encouraging doctors to be more confident and give more explanations. Keywords: hospital, brand management, Service-Dominant Logic, maintain leadership